2000
DOI: 10.1053/jhep.2000.8267
|View full text |Cite
|
Sign up to set email alerts
|

Human placenta sphingomyelinase, an exogenous acidic pH-optimum sphingomyelinase, induces oxidative stress, glutathione depletion, and apoptosis in rat hepatocytes

Abstract: Ceramide has been identified as a putative lipid messenger that mediates diverse cellular processes including cell death. Since glutathione (GSH) depletion is known to sensitize cells to many cytotoxic agents and as a result of the reported regulation of neutral sphyngomyelinase (NSMase) by GSH, the present study compared the role of individual SMases in the induction of oxidative stress, regulation of cellular GSH, and apoptosis of rat hepatocytes. Exposure of cultured rat hepatocytes to exogenous Bacillus ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 59 publications
(86 reference statements)
4
71
0
Order By: Relevance
“…Collectively, these data exclude C 6 -ceramide-mediated G 2 arrest as a result of DNA damage. Application of exogenous acidic SMase (ASMase; from human placenta) induced a transient elevation in endogenous ceramide (Figure 3a) as described elsewhere, 29 and was associated with a time-and dose-dependent arrest of RD cells in G 2 as determined from DNA cell cycle analysis (Figure 3a), BrdU incorporation (Figure 3b), phosphorylation of histone H3 (Figure 3c) and was associated with upregulation of p21 protein expression (Figure 3d). These observations were specific for ASMase since exogenous application of phospholipase C (PLC; from Bacillus cereus) or phospholipase D (PLD; from Steptomyces sp) did not modulate the cell cycle distribution of RD cells when used in the range 0-2 U/ml (data not shown).…”
Section: Resultsmentioning
confidence: 62%
“…Collectively, these data exclude C 6 -ceramide-mediated G 2 arrest as a result of DNA damage. Application of exogenous acidic SMase (ASMase; from human placenta) induced a transient elevation in endogenous ceramide (Figure 3a) as described elsewhere, 29 and was associated with a time-and dose-dependent arrest of RD cells in G 2 as determined from DNA cell cycle analysis (Figure 3a), BrdU incorporation (Figure 3b), phosphorylation of histone H3 (Figure 3c) and was associated with upregulation of p21 protein expression (Figure 3d). These observations were specific for ASMase since exogenous application of phospholipase C (PLC; from Bacillus cereus) or phospholipase D (PLD; from Steptomyces sp) did not modulate the cell cycle distribution of RD cells when used in the range 0-2 U/ml (data not shown).…”
Section: Resultsmentioning
confidence: 62%
“…The increased nSMase activity in the hepatocytes of old rats is dependent on the glutathione depletion, while the increased aSMase activity in the liver cells can deplete the glutathione stores (Garcia-Ruiz et al 2000). However, it has been recently shown that generation of reactive oxygen species an important step for aSMase activation in cells (Dumitru and Gulbins 2006;Charruyer et al 2005).The aSMase could be activated by the protein kinase Cδ (PKCδ), which is overexpressed under oxidative stress (Zeidan and Hannun 2007) and a premature aging disorderWerner syndrome (Massip et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mg 2ϩ -dependent NSMase and ASMase activities were determined from [N-methyl- 14 C]sphingomyelin (56.6 mCi/mmol, Amersham Biosciences, Piscataway, NJ) as described. 27 CDase activities were measured using 5 mol/L [ 14 C]ceramide (55 mCi/ mmol, ARC, St. Louis, MO) or C 12 -NBD ceramide (Molecular Probes, Eugene, OR) in 10 mmol/L Tris-HCl, pH 8.0 for the neutral/alkaline CDase or 0.5 mol/L acetate buffer, pH 4.5, for the acid CDase. 21,28 The GCS and SMS were determined as described previously.…”
Section: Methodsmentioning
confidence: 99%